2022
DOI: 10.12928/pharmaciana.v12i1.19667
|View full text |Cite
|
Sign up to set email alerts
|

The cholesterol-lowering activity of Averrhoa bilimbi L. leaves ethyl acetate fraction in hypercholesterolemic model

Abstract: Averrhoa bilimbi L. is used widely as spices and traditional medicine, which contained several chemical compounds such as alkaloid, flavonoid, saponin, and tannin. The aim of this study is to discover the best dose of ethyl acetate fraction from A.bilimbi leaves, which have pharmacology activity on total cholesterol and triglycerides in the hypercholesterolemic model. Thirty adult male white mice were divided into six groups; each group was containing five animals. Five groups were given high-fat diet foods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…[18][19][20][21][22][23] The presence of alkaloids and other bioactive compounds invokes the medicinal characteristics of the plants and their therapeutic use in various pharmacopoeias. 24,25 Sub-acute toxicity, animal observation, body weight, food intake and water consumption measurement A sub-acute oral toxicity study in BALB/c mice indicated zero mortality after repeated VALAF administration for 21 days. There was, however, a change in behaviour, such as grooming and sleeping.…”
Section: Physicochemical and Phytochemical Analysismentioning
confidence: 99%
“…[18][19][20][21][22][23] The presence of alkaloids and other bioactive compounds invokes the medicinal characteristics of the plants and their therapeutic use in various pharmacopoeias. 24,25 Sub-acute toxicity, animal observation, body weight, food intake and water consumption measurement A sub-acute oral toxicity study in BALB/c mice indicated zero mortality after repeated VALAF administration for 21 days. There was, however, a change in behaviour, such as grooming and sleeping.…”
Section: Physicochemical and Phytochemical Analysismentioning
confidence: 99%
“…On day 0, 1, 3 and 5 the blood was taken from the ocular sinus and centrifuged at 3000 rpm for 10 min, with the plasma remained. Total cholesterol (TC) and triglyceride (TG), levels in plasma were analyzed according to manufacturer procedures (Sigma-Aldrich, St. Louis, USA) [19].…”
Section: Lipid Profile Measurementmentioning
confidence: 99%